2023
DOI: 10.1038/s41586-022-05583-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of broad-spectrum β-lactam resistance in Staphylococcus aureus

Abstract: Broad-spectrum β-lactam antibiotic resistance in Staphylococcus aureus is a global healthcare burden1,2. In clinical strains, resistance is largely controlled by BlaR13, a receptor that senses β-lactams through the acylation of its sensor domain, inducing transmembrane signalling and activation of the cytoplasmic-facing metalloprotease domain4. The metalloprotease domain has a role in BlaI derepression, inducing blaZ (β-lactamase PC1) and mecA (β-lactam-resistant cell-wall transpeptidase PBP2a) expression3–7. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…The COTT genome was the only C . oranimense genome containing the bla regulator protein BlaR1 (K02172), which largely controls β-lactam antibiotic resistance 118 and membrane carboxypeptidase (penicillin-binding protein) which would render COTT resistant to penicillin ( Additional file 2: Supplementary Table S18 and S28 ). There were also three phenicol and two bacteriocin genes identified in COTT ( Additional file 2: Table S28 ).…”
Section: Resultsmentioning
confidence: 99%
“…The COTT genome was the only C . oranimense genome containing the bla regulator protein BlaR1 (K02172), which largely controls β-lactam antibiotic resistance 118 and membrane carboxypeptidase (penicillin-binding protein) which would render COTT resistant to penicillin ( Additional file 2: Supplementary Table S18 and S28 ). There were also three phenicol and two bacteriocin genes identified in COTT ( Additional file 2: Table S28 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the resistance of S. aureus to β-lactam antibiotics is controlled by the BlaR13 receptor that senses β-lactams through acylation of its sensor domain, inducing transmembrane signaling and activation of the cytoplasm-oriented metalloprotease domain. This domain induces the expression of blaZ (β-lactamase PC1) and mecA (β-lactam-resistant cell wall transpeptidase PBP2a) [ 80 ], the latter encoding the alternative penicillin-binding protein, PBP2A, which is insensitive to antibiotics. Another reason for resistance is due to additional genetic adjustments to develop a high level of resistance [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical S. aureus strains, the membrane-embedded receptor BlaR1 senses β-lactams through the acylation of its sensor domain [ 55 ], inducing transmembrane signaling and activation of a cytoplasmic-facing zinc metalloprotease domain [ 56 ]. The activated zinc metalloprotease domain then cleaves the repressor protein BlaI [ 57 , 58 ], inducing the expression of β-lactamase [ 59 , 60 ].…”
Section: Molecular Mechanisms Of β-Lactam Resistancementioning
confidence: 99%
“… Regulation of blaZ and mecA . The bla or mec gene clusters encode regulatory systems that sense β-lactams on the cell surface through a membrane-embedded sensor–inducer BlaR1 (PDB: 1XA7)/MecR1 (PDB:6O9S) [ 60 ]. The signal generated by β-lactam detection induces the cleavage of a cytoplasmic transcriptional repressor BlaI/MecI.…”
Section: Figurementioning
confidence: 99%